2016
DOI: 10.1021/acs.jpcc.5b09704
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Behavior of Halide Ions on the Au(111) Electrode Surface in Ionic Liquids Using Surface X-ray Scattering

Abstract: The behavior of halide ions on the Au(111) electrode surface in two ionic liquids (ILs), 1-buthyl-1-methylpyrrolidiniun bis(trifluoromethylsulfonyl)amide ([BMP]TFSA) and 1buthyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide ([BMIM]TFSA), was investigated by monitoring the structure of the electrode surface. The potential dependences of the Xray diffraction intensity, which originate from the Au( 111)-(1 × 1) structure and the surface normal structure, were measured simultaneously with cyclic voltammogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…They revealed also that the interfacial structure is influenced not only by the concentration of ILs but also by the nature of the anions and cations in the composition of the ILs. 45 In brief, these investigations established that the adsorption of anions and cations at the gold surface can significantly affect the chemical reactivity of the electrode. 46…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They revealed also that the interfacial structure is influenced not only by the concentration of ILs but also by the nature of the anions and cations in the composition of the ILs. 45 In brief, these investigations established that the adsorption of anions and cations at the gold surface can significantly affect the chemical reactivity of the electrode. 46…”
Section: Introductionmentioning
confidence: 99%
“…They revealed also that the interfacial structure is influenced not only by the concentration of ILs but also by the nature of the anions and cations in the composition of the ILs. 45 In brief, these investigations established that the adsorption of anions and cations at the gold surface can significantly affect the chemical reactivity of the electrode. 46 At the molecular level, more light can be shed onto the adsorption mechanism, reactivity, and the ordering of various ILs at metal surfaces using quantum chemical calculations and molecular dynamics with the help of force-field-based simulations.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In the field of IL electrochemistry, ILs consisting of alkylmethylimidazolium ([C n mim] + ) or butylmethylpyrrolidinium ([BMP] + ) cations and bistrifluoromethylsulfonylamide ([Tf 2 N] ¹ ) anions are often used because of their high chemical stability. [9][10][11][12][13][14][15][16][17] The electrochemical interfaces of ILs have been studied using various methods, such as sum frequency generation (SFG), 9 X-ray photoelectron spectroscopy (XPS), 10,11 surface X-ray scattering (SXS), 12,13 infrared spectroscopy, 14 and scanning tunneling microscopy (STM). [15][16][17] However, to our best knowledge, details on the adsorption and adlayer structures of ILs are still limited owing to the weak adsorption of [Tf 2 N] ¹ , although highly ordered adsorption of cations, such as [C 6 mim] + and [BMP] + , has been observed at room temperature using video STM.…”
Section: Introductionmentioning
confidence: 99%
“…22 Further, it was found that halide anions are coadsorbed with IL molecules and increase the mobility of surface atoms; however, the surface structure is mainly governed by adsorbed IL molecules. 23 These studies proved that quantum beam measurements are suitable for the analysis of the structure of the IL/electrode interface since they are non-destructive techniques and measurements can be carried out under electrochemically ideal conditions. We have subsequently investigated the structure of EDL formed in [BMIM]TFSA on Si(100) electrode surface using neutron reflectivity.…”
mentioning
confidence: 93%